Pengaruh Lingkungan Bahasa Terhadap Kemahiran Berbicara Bahasa Arab bagi Non-Penutur Asli di Institut Muslim Cendekia: The Impact of Linguistic Environment on Arabic Speaking Skills Among Non-Native Speakers at Muslim Cendekia Institute - Muhammad Furqon Almurni; Jajang Komaludin; Jajat Sudrajat; Fathi Syauqi; Zakiy Alfarid (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
The mastery of speaking skills (mahārah kalām) is a central aspect of Arabic language learning for non-native speakers, which necessitates an active and authentic communicative environment. This study aims to empirically examine and prove the magnitude of the influence of the language environment on the Arabic speaking proficiency of students at the Muslim Cendekia Institute (IMC), Sukabumi. A quantitative correlational approach was employed. Sampling was conducted using a purposive sampling technique, restricted exclusively to second-semester male students who had resided in the boarding system for eight months. From a population of 115 students, this study involved 90 respondents. Data collection utilized questionnaire instruments, with initial validation performed using Microsoft Excel, while reliability testing and linear regression analysis were processed through SPSS 25 software. The results demonstrate that the measurement instrument is highly reliable, with a Cronbach's Alpha value of 0.955. Regression analysis indicates a positive and significant effect of the language environment on speaking proficiency, as evidenced by a significance value of 0.000 ($p < 0.05$) and an F-value of 138.397. The coefficient of determination ($R^2$) of 0.611 confirms that the language environment contributes 61.1% to the enhancement of speaking proficiency, while the remaining 38.9% is influenced by other factors outside this model. These findings provide an empirical contribution to the discourse of Arabic language education, specifically by reinforcing the theory that an immersive boarding system requiring target language interaction is a highly effective strategy and can serve as a reference model for higher educational institutions in accelerating language acquisition.